2019
DOI: 10.1093/humrep/dez204
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the stromal antigen 3 (STAG3) gene cause male infertility due to meiotic arrest

Abstract: STUDY QUESTION Are sequence variants in the stromal antigen 3 (STAG3) gene a cause for non-obstructive azoospermia (NOA) in infertile human males? SUMMARY ANSWER Sequence variants affecting protein function of STAG3 cause male infertility due to meiotic arrest. WHAT IS KNOWN ALREADY In both women and men, STAG3 encodes for a meiosis-specific protein that is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 23 publications
0
39
0
Order By: Relevance
“…In the initial MERGE study, the WES data of 60 highly selected, azoospermic infertile patients with unexplained, complete, bilateral germ cell arrest at the spermatocyte stage were screened for rare (MAF < 0.01 according to gnomAD-database 22 ), biallelic LoF variants. Two patients were subsequently excluded from this study, because likely causal variants in other genes had been identified in parallel: patient M870 had compound heterozygous variants in STAG3, 23 and patient M1401 had a heterozygous LoF variant in SYCP2 . 24 The prioritized genes in the remaining 58 patients were analyzed with regard to the level of expression in the testes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the initial MERGE study, the WES data of 60 highly selected, azoospermic infertile patients with unexplained, complete, bilateral germ cell arrest at the spermatocyte stage were screened for rare (MAF < 0.01 according to gnomAD-database 22 ), biallelic LoF variants. Two patients were subsequently excluded from this study, because likely causal variants in other genes had been identified in parallel: patient M870 had compound heterozygous variants in STAG3, 23 and patient M1401 had a heterozygous LoF variant in SYCP2 . 24 The prioritized genes in the remaining 58 patients were analyzed with regard to the level of expression in the testes.…”
Section: Resultsmentioning
confidence: 99%
“…The first was the X-chromosomal gene TEX11 , 6, 26 which is, according to a current structured assessment, one of only a few genes with strong clinical validity for an association with NOA. 7 Another example is the autosomal gene STAG3 , which has only recently been described in publications by us and others in parallel, 23, 27 and its clinical validity is currently ‘moderate’. Most of the proteins involved in DNA recombination, including M1AP , are highly evolutionarily conserved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it has been reported that two SNPs (rs1727130 and rs1052482) located in the 3'-UTR of the STAG3 gene were identi ed to be associated with NOA in Korean population [30]. Furthermore, homozygous or compound-heterozygous variants of the STAG3 gene have been identi ed in NOA patients from Germany, Spain, and Australia [31][32][33]. In this study, we did not identify the same variants which may be due to the small sample size and ethnic diversity.…”
Section: Discussionmentioning
confidence: 99%